2014
DOI: 10.1088/0004-6256/147/6/161
|View full text |Cite
|
Sign up to set email alerts
|

TRANSMISSION SPECTROSCOPY OF THE HOT JUPITER WASP-12b FROM 0.7 TO 5 μm

Abstract: Since the first report of a potentially non-solar carbon-to-oxygen ratio (C/O) in its dayside atmosphere, the highly irradiated exoplanet WASP-12b has been under intense scrutiny and the subject of many follow-up observations. Additionally, the recent discovery of stellar binary companions ∼1 ′′ from WASP-12 has obfuscated interpretation of the observational data. Here we present new ground-based multi-object transmissionspectroscopy observations of WASP-12b that we acquired over two consecutive nights in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(233 citation statements)
references
References 40 publications
(80 reference statements)
14
215
3
1
Order By: Relevance
“…These results are similar to the values reached with GEMINI-N/GMOS in comparable spectrophotometric studies (G13; Stevenson et al 2014). The properties of the chromatic light curves are summarized in Table A.1.…”
Section: Creation Of Light Curvessupporting
confidence: 88%
“…These results are similar to the values reached with GEMINI-N/GMOS in comparable spectrophotometric studies (G13; Stevenson et al 2014). The properties of the chromatic light curves are summarized in Table A.1.…”
Section: Creation Of Light Curvessupporting
confidence: 88%
“…More recent observations of the day-side emission spectrum of HD 209458b, call the existence of the inversion layer into question (Zellem et al 2014;Diamond-Lowe et al 2014). Interestingly, Stevenson et al (2014) observed molecular absorption features in the near-infrared dayside spectrum of Wasp-12b, possibly attributable to TiO. This contrasts with the optical transmission spectra of the same planet, as put forth by Sing et al (2013).…”
Section: Introductionmentioning
confidence: 87%
“…While the host star is fairly faint (V = 12), WASP-12b's close semimajor axis and large radius (a = 0.0234 au, R R 1.90 Collins et al 2017) make it an excellent target for detailed study. Transit observations of WASP-12b range from 0.3 to 4.5μm, and eclipse observations range from 0.9 to 8.0μm (e.g., Hebb et al 2009;López-Morales et al 2010;Campo et al 2011;Madhusudhan et al 2011;Cowan et al 2012;Crossfield et al 2012;Copperwheat et al 2013;Föhring et al 2013;Sing et al 2013;Swain et al 2013;Stevenson et al 2014aStevenson et al , 2014bCroll et al 2015;Sing et al 2016). This work presents the first optical eclipse measurement of WASP-12b.…”
Section: Introductionmentioning
confidence: 92%